2022
DOI: 10.3390/ijerph19127081
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Sociodemographic Factors on Symptoms of Anxiety, the Level of Aggression and Alcohol Consumption in the Time of the COVID-19 Pandemic among Polish Respondents

Abstract: The COVID-19 pandemic has had a significant impact on the mental health of most of the world’s population. The authors of this study decided to identify differences in the intensity of anxiety, aggression and alcohol consumption within the study population. The study was conducted via an Internet survey. It uses Polish adaptations of international scales to assess anxiety (GAD-7), aggression (Buss and Perry Aggression Scale) and alcohol consumption (AUDIT test). A total of 538 people were examined. The surveye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…In the comparative analysis of alcohol consumption levels, it is noteworthy that more male respondents consume larger amounts of alcohol statistically. This fact is not surprising, as it fits the characteristics of the alcohol consumption pattern ( Manwell et al, 2002 ) that is present in Poland and coincides with the reports of a study conducted at the beginning of the COVID-19 pandemic ( Florek et al, 2022 ).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In the comparative analysis of alcohol consumption levels, it is noteworthy that more male respondents consume larger amounts of alcohol statistically. This fact is not surprising, as it fits the characteristics of the alcohol consumption pattern ( Manwell et al, 2002 ) that is present in Poland and coincides with the reports of a study conducted at the beginning of the COVID-19 pandemic ( Florek et al, 2022 ).…”
Section: Discussionsupporting
confidence: 89%
“…With reference to the project carried out at the beginning of the COVID-19 pandemic in Poland, it can be concluded that these differences remained essentially unchanged (Florek et al, 2022). In terms of physical and verbal aggression they have strengthened, while in terms of anger they have weakened.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Prior to the outbreak of the COVID-19 pandemic, one in five Europeans was addicted to alcohol, with the prevalence ranging from 0,1 to 6.6% [ 13 , 14 ]. Studies conducted during the pandemic demonstrated an increased frequency and quantity of alcohol consumption in many European countries, including the United Kingdom, Germany, and Poland [ 15 , 16 , 17 ]. The consequences of abuse for public health will take an even greater toll in the upcoming years.…”
Section: Resultsmentioning
confidence: 99%
“…Corticosteroids and alcohol use are the major risk factors for bone necrosis. When put together, both of them are the causative factors found in up to 80% of cases of ON [ 17 ]. For both agents, the risk is time- and dose-dependent [ 19 , 40 , 51 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%